WOJNA W IRAKU W ŚWIETLE DOKTRYNY BUSHA - Kaczmarek, Piotr (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article presents changes in American foreign policy after 11th 2001 and is concerned the George W. Bush’s Middle East policy. The goal of the text is presenting how the Bush doctrine leaded to war in Iraq. After the short introduction about US Middle East policy the text explains fundamental parts of doctrine and describes the most important G. W. Bush speeches and National Security Strategies from 2002 and 2006. This part is dedicated on war on terror, axis of evil and preventive war. The next part try to identify actual and the official and publically stated causes the 2003 invasion of Iraq. The article ends with the analysis the cost of Iraq war.